Cyanobacterial type I CRISPR-Cas systems: distribution, mechanisms, and genome editing applications - Zhang, Yongjiu; Yang, Shuxiao; Zheng, Xianliang; Tan, Xiaoming (Frontiers in Bioengineering and Biotechnology, 2025)
Cyanobacteria, renowned for their photosynthetic capabilities, serve as efficient microbial chassis capable of converting carbon dioxide into a spectrum of bio-chemicals. However, conventional genetic manipulation strategies have proven incompatible with the precise and systematic modifications required in the field of cyanobacterial synthetic biology. Here, we present an in-depth analysis of endogenous CRISPR-Cas systems within cyanobacterial genomes, with a particular focus on the Type I systems, which are the most widely distributed. We provide a comprehensive summary of the reported DNA defense mechanisms mediated by cyanobacterial Type I CRISPR-Cas systems and their current applications in genome editing. Furthermore, we offer insights into the future applications of these systems in the context of cyanobacterial genome editing, underscoring their potential to revolutionize synthetic biology approaches.